Economic Status and Inter-Group Disparities among Scheduled Castes, Scheduled Tribes and Other Backward Classes: A Review (International Journal of Food and Nutritional Sciences, 2024)
This study examines the economic status of Scheduled Castes (SCs), Scheduled Tribes (STs) and Other Backward Classes (OBCs in Nuapada district of Odisha, a region characterized by persistent poverty and structural backwardness. Using a descriptive and comparative research design, the study draws on secondary data from the Census of India, National Sample Survey (NSS), Periodic Labour Force Survey (PLFS), and District Statistical Handbooks, supplemented by existing empirical literature. Key economic indicators such as employment patterns, income levels, poverty incidence, land ownership, and access to productive resources are analyzed to assess inter-group disparities. The findings reveal that SC and ST communities face deeper and more persistent economic deprivation compared to OBCs, primarily due to landlessness, insecure livelihoods, and limited access to institutional support. ST households emerge as the most vulnerable group, affected by tenure insecurity, geographic isolation, and dependence on subsistence agriculture and forest-based livelihoods. While OBC communities display relatively better economic conditions, a significant proportion remains vulnerable due to low agricultural productivity and informal employment. Government welfare schemes such as MGNREGA, PDS, and PMAY-G have contributed to income stabilization and food security; however, their impact remains largely short-term due to implementation challenges and lack of livelihood diversification. The study underscores the need for region-specific and social-group-sensitive policy interventions to promote inclusive and sustainable economic development in Nuapada district.